X-ray scattering from light-driven spin fluctuations in a doped Mott insulator - Yao Wang (Nature Portfolio, 2021)
The manipulation of spins with ultrafast lasers is a promising route to control the properties of a wide variety of quantum materials. Here, the authors present a simulation of Floquet-engineered spin fluctuations in a correlated system and of their fingerprints in ultrafast inelastic X-ray scattering experiments.